Effects of off-line auricular transcutaneous vagus nerve stimulation (taVNS) on a short-term memory task: a pilot study - Fisicaro, Francesco; Cortese, Klizia; Bella, Rita; Pennisi, Manuela; Lanza, Giuseppe; Yuasa, Kaoru; Ugawa, Yoshikazu; Terao, Yasuo (Frontiers in Aging Neuroscience, 2025)
IntroductionOne of the commonly used indices of short-term memory (STM) is the digit span task. Prior studies have proposed pupil dilation as a measure of task engagement and as a promising biomarker of vagal activation. Transcutaneous auricular vagus nerve stimulation (taVNS) is a novel non-invasive brain stimulation technique which might be used to improve cognition and modulate pupil size through its effects on the noradrenergic release in the locus coeruleus. No previous study has investigated the effects of off-line taVNS on a digit span task. With this single-blind, sham-controlled, crossover design trial, we aimed to assess whether taVNS was able to improve the digit span score, as well as to modulate the pupillary response to cognitive load in a sample of 18 elderly Japanese volunteers with no self-reported cognitive impairments.ResultsSubjects were randomized to receive either real or sham taVNS during a digit span task while recording the pupil size, and then switched over to the other treatment group. We found that real stimulation significantly reduced the mean number of errors performed at span length 7, 8, and 9 (–0.83, –0.90, and –0.39, respectively compared to pre-stimulation values, and –0.71, –1.08, and –0.79, respectively, compared to sham stimulation). Additionally, real taVNS stimulation slightly but significantly increased the pupil size at all span lengths during the encoding period of the task, with larger effects for span 7–10 compared to pre-stimulation, and for span 5–10 compared to sham. No effect over the pupil size was found during the recall period.DiscussionOur results suggest that taVNS might selectively improve the cognitive performance during the encoding phase of the task. Although further studies are needed to better clarify the optimal stimulation parameters, findings from this study could support the use of taVNS as a safe neuromodulation technique to improve cognitive function.